Intellectual Capital Performance: A Comparative Study between Financial and Non-Financial Industry of Indonesian Biggest Companies - Ulum, Ihyaul; Rizqiyah, Rizqiyah; Jati, Ahmad Waluya (International Journal of Economics and Financial Issues, 2016)
The aim of this study is to analyze the intellectual capital performance (ICP) of financial and non-financial industry of Indonesian biggest companies. ICP was measured with Modified Value Added Intellectual Coefficient (MVAIC) constucted by Ulum et al. (2014a) which is based on Pulic’s model (Pulic, 1998). MVAIC is a comprehensive tool to measure the performance of intellectual capital (IC). Data were taken from 50 biggest market capitalizations listed on the Indonesia Stock Exchange (IDX) for the period of 2007-2014. The result indicates that the ICP of companies in the non-financial industry is higher than the ICP of companies in financial industry. This result disputes that financial industry is one of IC intensive sector as identified by Firer and Williams (2003). Keywords: intellectual capital, intellectual capitalperformance, MVAIC, financial industry. JEL Classifications: E44, G23